ZmOrphan94 Transcription Factor Downregulates ZmPEPC1 Gene Expression in Maize Bundle Sheath Cells - Górska, Alicja M.; Gouveia, Paulo; Borba, Ana Rita; Zimmermann, Anna; Serra, Tânia S.; Carvalho, Pedro; Lourenço, Tiago F.; Oliveira, M. Margarida; Peterhänsel, Christoph; Saibo, Nelson J. M. (Frontiers in Plant Science, 2021)
Spatial separation of the photosynthetic reactions is a key feature of C4 metabolism. In most C4 plants, this separation requires compartmentation of photosynthetic enzymes between mesophyll (M) and bundle sheath (BS) cells. The upstream region of the gene encoding the maize PHOSPHOENOLPYRUVATE CARBOXYLASE 1 (ZmPEPC1) has been shown sufficient to drive M-specific ZmPEPC1 gene expression. Although this region has been well characterized, to date only few trans-factors involved in the ZmPEPC1 gene regulation were identified. Here, using an yeast one-hybrid approach, we have identified three novel maize transcription factors ZmHB87, ZmCPP8, and ZmOrphan94 as binding to the ZmPEPC1 upstream region. Bimolecular fluorescence complementation assays in maize M protoplasts unveiled that ZmOrphan94 forms homodimers and interacts with ZmCPP8 and with two other ZmPEPC1 regulators previously reported, ZmbHLH80 and ZmbHLH90. Trans-activation assays in maize M protoplasts unveiled that ZmHB87 does not have a clear transcriptional activity, whereas ZmCPP8 and ZmOrphan94 act as activator and repressor, respectively. Moreover, we observed that ZmOrphan94 reduces the trans-activation activity of both activators ZmCPP8 and ZmbHLH90. Using the electromobility shift assay, we showed that ZmOrphan94 binds to several cis-elements present in the ZmPEPC1 upstream region and one of these cis-elements overlaps with the ZmbHLH90 binding site. Gene expression analysis revealed that ZmOrphan94 is preferentially expressed in the BS cells, suggesting that ZmOrphan94 is part of a transcriptional regulatory network down-regulating ZmPEPC1 transcript level in the BS cells. Based on both this and our previous work, we propose a model underpinning the importance of a regulatory mechanism within BS cells that contributes to the M-specific ZmPEPC1 gene expression.